Copper concentration in erythrocytes, platelets, plasma, serum and urine: influence of physical training - Víctor Toro-Román; Jesús Siquier-Coll; Ignacio Bartolomé; Francisco J. Grijota; Diego Muñoz; Marcos Maynar-Mariño (Taylor & Francis Group, 2021)
Background Physical training produces changes in the extracellular and intracellular concentrations of trace minerals elements. To our knowledge, only three compartments have been studied simultaneously. The aim of the present study was to analyze the influence of physical training on extracellular (serum, plasma and urine) and intracellular (erythrocytes and platelets) concentrations of Copper (Cu). Methods Forty young men participated in this study. The participants were divided into a training group (TG; n = 20; 18.15 ± 0.27 years; 68.59 ± 4.18 kg; 1.76 ± 0.04 m) and a control group (CG; n = 20; 19.25 ± 0.39 years; 73.45 ± 9.04 kg; 1.79 ± 0.06 m). The TG was formed by semi-professional soccer players from a youth category with a regular training plan of 10 h/week. All of them had been participating in high level competitions and had trained for at least 5 years. Plasma, serum, urine, erythrocyte and platelet samples of Cu were obtained and analyzed by inductively coupled plasma mass spectrometry (ICP-MS). Results The TG showed lower concentrations of Cu in erythrocytes (p < 0.05) despite similar intakes. There were no significant differences in Cu concentrations in plasma, serum, urine and platelets although the trend was similar to that observed in erythrocytes. Conclusions The assessment of trace element concentrations should be carried out in both extracellular and intracellular compartments to obtain a proper evaluation and to identify possible deficiencies of the element. We believe that additional Cu supplementation is needed in athletes who perform physical training regularly.